Akibat Kemurtadan Kepastian Keselamatan Hilang (Studi Eksegesa Kitab Ibrani 5:11 – 6:8) - Daniel Boedhi Oetomo (International Forum of Researchers and Lecturers, 2024)
The certainty of of being saved is the most important thing that God has given to humans. However, people often refuse to be led and enter into God’s plan. As a result of refusing to be led by God, many of God’s people fall away and ultimately turn against God. Man leaves God and turns to truths outside God considered more correct. Same people think that God is all-loving and forgiving and cannot possibly bear to punish people who believe Him, even though they refuse to be led by God. How is the salvation of people who refuse to be led by God and even then fall away ? The research in this thesis begins by studying and explaining the meaning of apostasy and the reasons why someone can become apostate. Continuing with the possibility of whether or not sameone can apostate from God. To complete it, the author raises several views of theological figures regarding the possibility of apostasy. The author describes with an exegetical study parts of the Bible verse in the book of Hebrew 5:11 -6:8 which are often used as an cirgue for theological controversy, regarding the possibility of apostasy and loss safety. Conclusions are obtained by comparing, analyzing and provides an interpretation based on the analogy method of faith, the Bible as a basis for measuring truth. Realizing that humans are obliged to submit themselves to God and obey God’s statements, the author also used methods Neo-Supernatural dialectics. From the results of research exegetically and by proposing premises so the author can conclude that if sameone who has believed in the Lord Jesus Christ then apostatizes, then the certainty of his salvation will be lost.